2007
DOI: 10.1103/physreva.76.011402
|View full text |Cite
|
Sign up to set email alerts
|

Isolated sub-100aspulse generation via controlling electron dynamics

Abstract: A new method to coherently control the electron dynamics is proposed using a few-cycle laser pulse in combination with a controlling field. It is shown that this method not only broadens the attosecond pulse bandwidth, but also reduces the chirp, then an isolated 80-as pulse is straightforwardly obtained and even shorter pulse is achievable by increasing the intensity of the controlling field. Such ultrashort pulses allow one to investigate ultrafast electronic processes which have never be achieved before. In… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
72
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 151 publications
(73 citation statements)
references
References 25 publications
0
72
0
1
Order By: Relevance
“…One of them, the HHG is well known due to the fact that it provides a new type of coherence light source of extremely short wavelength that can be widely used in many fields such as attosecond pulse generation [7][8][9][10][11], plasma spectroscopy [12], and X-ray fluorescence analysis [13]. A semiclassical three-step model successfully explains the HHG process [14].…”
Section: ι Introductionmentioning
confidence: 97%
“…One of them, the HHG is well known due to the fact that it provides a new type of coherence light source of extremely short wavelength that can be widely used in many fields such as attosecond pulse generation [7][8][9][10][11], plasma spectroscopy [12], and X-ray fluorescence analysis [13]. A semiclassical three-step model successfully explains the HHG process [14].…”
Section: ι Introductionmentioning
confidence: 97%
“…Compared with the intensity gating, PG technique allows much broader supercontinuum generation, not only in the cutoff region but also in the plateau region. Previous studies demonstrated that a weak second harmonic (SH) field can be added to modulate the inner dynamics of the HHG process [11] and, even more importantly, to manipulate the ionization step for efficient isolated attosecond burst, which is served as two-color ionization gating [12]. Chang et al combined the two-color field and the PG techniques to simultaneously control ionization and recombination steps, dubbed as double optical gating, and generated an efficient broadband supercontinuum in the plateau [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…During the recombination process, a photon with energy equaling to the ionization potential plus the kinetic energy is emitted. Various gating schemes have been proposed to produce isolated attosecond pulses according to the model, such as using a few-cycle laser [5,6], polarization gating [7][8][9][10][11][12], ionization gating [13,14] and two-color or multi-color field [15][16][17][18][19][20][21][22][23][24][25][26], and so on.…”
Section: Introductionmentioning
confidence: 99%